Modulating the photoluminescence of bridged silsesquioxanes incorporating Eu(3+)-complexed n,n '-diureido-2,2 '-bipyridine isomers: application for luminescent solar concentrators - Graffion, Julien (2013)
Two new urea-bipyridine derived bridged organosilanes (P5 and P6) have been synthesized and their hydrolysis-condensation under nucleophilic catalysis in the presence of Eu(3+) salts led to luminescent bridged silsesquioxanes (M5-Eu and M6-Eu). An important loading of Eu(3+) (up to 11%(w)) can be obtained for the material based on the 6,6'-isomer. Indeed the photoluminescence properties of these materials, that have been investigated in depth (photoluminescence (PL), quantum yield, lifetimes), show a significantly different complexation mode of the Eu(3+) ions for M6-Eu, compared with M4-Eu (obtained from the already-reported 4,4'-isomer) and M5-Eu. Moreover, M6-Eu exhibits the highest absolute emission quantum yield value (0.18 +/- 0.02) among these three materials. The modification of the sol composition upon the addition of a malonamide derivative led to similar luminescent features but with an increased quantum yield (026 +/- 0.03). In addition, M6-Eu can be processed as thin films by spin-coating on glass substrates, leading to plates coated by a thin layer (similar to 54 nm) of Eu(3+)-containing hybrid silica exhibiting one of the highest emission quantum yields reported so far for films of Eu(3+)-containing hybrids (0.34 +/- 0.03) and an interesting potential as new luminescent solar concentrators (LSCs) with an optical conversion efficiency of similar to 4%. The ratio between the light guided to the film edges and the one emitted by the surface of the film was quantified through the mapping of the intensity of the red pixels (in the RGB color model) from a film image. This quantification enabled a more accurate estimation of the transport losses due to the scattering of the emitted light in the film (0.40), thereby correcting the initial optical conversion efficiency to a value of 1.7%.